Developing future scenarios: Business students and librarians employing foresight techniques in tandem during course support. Issue 3 (1st October 2016) - Pietraszewski, Barbara A.
ABSTRACT: In the process of providing support to the undergraduate students and instructors of a research-intensive future studies course, librarians at the University of Notre Dame used the proactive decision-making framework taught to the students and conducted their own environmental scan, current assessment, and trend analysis in order to determine expected and plausible alternative future support scenarios for the course. This article reviews the evolving partnership and describes a process that has resulted and will continue to result in improved decision making regarding the allocation of resources to this course and all others supported by the business library.